Condor comeback - Montgomery, Sy (Scientists in the field., 2020)
Details the fight to protect the endangered California condor after they officially went extinct in the wild in 1987, and presents the scientists, volunteers, and citizens who have dedicated their work to protecting California condors. Explains the legislation that has been put in place to protect them and the outreach done through schools to educate kids about California condors, and examines their importance in Native American cultures. Includes color photographs, a map, a timeline, and additional resources.